Theory of Planned Behavior: Determinants of the Use of Modern Family Planning Method - Agus, Yuliana; Pamungkasari, Eti Poncorini; Soemanto, RB. (Journal of Maternal and Child Health, 2019)
Background: The use of contraception tool is one of the factors that affect fertility. It is influ